PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN MENGGUNAKAN KOMPONEN-KOMPONEN RANCANGAN PEMBELAJARAN QUANTUM TEACHING DI SEKOLAH DASAR - Satriani, Anri Mira (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research background of the fact that learning in elementary school is often dominated by the teacher as a source of information based on observation the researchers found low student learning outcomes. Here researchers used components of Quantum Teaching lesson plan. The purpose of this research to improve learning outcomes by using a Civics lesson plan components Quantum Teaching in Elementary School fifth grade 58 Batu Hampar Lubuk Basung - Agam. The study was Classroom Action Research (CAR). This study used qualitative and quantitative approaches. This study is the PTK (Classroom Action Research), which consists of the second cycle of 4 meetings with the four components of planning, action, observation and reflection. The data source is the implementation process of learning the lesson plan components Quantum Teaching in Elementary School fifth grade 58 Batu Hampar Lubuk Basung - Agam. Subjects were students of class V were a total of 11 people. The results showed the first cycle I and II that the meeting of the RPP assessment scores obtained 71 and 78, from the aspect of teacher earned a score of 63.5 and 71, from the aspect of students earned scores of 50 and 67, students' cognitive nilsi obtained were 67 and 74 , affective values ​​56 and 75, while the value psikomotornya was 59 and 63. While on the second cycle of assessment RPP scores obtained 93 and 96, from the aspect of teacher earned a score of 83 and 92, from the aspect of the students obtained a score of 79 and 87, students' cognitive nilsi obtained were 81 and 86, the affective value of 89 and 95, while psikomotornya values ​​were 76 and 86, it appears that student learning outcomes increased from cycle I to cycle II. Thus it was revealed that the use of learning design components Quantum Teaching Civics can improve learning outcomes in fifth grade elementary school students 58 Batu Hampar Lubuk Basung – Agam. Kata kunci: hasil belajar, PKn, komponen-komponen rancangan pembelajaran quantum teaching